2012
DOI: 10.2203/dose-response.12-041.lee
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Low dose Radiation on Differentiation of Bone Marrow Cells into Dendritic Cells

Abstract: ᮀ Low dose radiation has been shown to be beneficial to living organisms using several biological systems, including immune and hematopoietic systems. Chronic low dose radiation was shown to stimulate immune systems, resulting in controlling the proliferation of cancer cells, maintain immune balance and induce hematopoietic hormesis. Since dendritic cells are differentiated from bone marrow cells and are key players in maintaining the balance between immune activation and tolerance, it may be important to furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…The state of immunity has a very important role in the defense against tumor formation and growth. However, its effect is characterized as a two-edged sword, as the direction of effect is dependent on many factors [97][98][99][100][101]. Tumor-directed immune reactants in low doses stimulate tumor growth, while it blocks tumor growth in higher doses [102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…The state of immunity has a very important role in the defense against tumor formation and growth. However, its effect is characterized as a two-edged sword, as the direction of effect is dependent on many factors [97][98][99][100][101]. Tumor-directed immune reactants in low doses stimulate tumor growth, while it blocks tumor growth in higher doses [102][103][104].…”
Section: Discussionmentioning
confidence: 99%
“…At this point, we consider how low-dose irradiation might affect the function of Sam68 in the immune system. In fact, many previous reports have shown that low-dose irradiation improves the immune function, based on radiation hormesis theory [ 29 31 ]. For instance, low-dose irradiation has been known to facilitate anti-tumor cytotoxicity of natural killer cells without influencing cellular proliferation [ 30 ] or apoptosis and to induce immune-stimulatory responses in human primary monocytes [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A low dose of TBI (0.2 Gy) was found to increase surface expression of CD80, CD86, MHC class I, and MHCII on immature and mature DCs, but suppressed the antigen uptake capacity as well as IL-12 secretion, suggesting a shift toward immune tolerance [ 92 ]. Mature DCs given a high dose of irradiation (30 Gy) secreted less IL-12, showed remarkable resistance against radiation-induced apoptosis and were less effective in a mixed lymphocyte reaction [ 93 ].…”
Section: Modulation Of the Tumor Microenvironment By Chronic Stresmentioning
confidence: 99%